2019
DOI: 10.1159/000497289
|View full text |Cite
|
Sign up to set email alerts
|

Technical Considerations in the Freezing, Low-Temperature Storage and Thawing of Stem Cells for Cellular Therapies

Abstract: The commercial and clinical development of cellular therapy products will invariably require cryopreservation and frozen storage of cellular starting materials, intermediates and/or final product. Optimising cryopreservation is as important as optimisation of the cell culture process in obtaining maximum yield and a consistent end-product. Suboptimal cryopreservation can lead not only to batch-to-batch variation, lowered cellular functionality and reduced cell yield, but also to the potential selection of subp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 63 publications
1
98
0
3
Order By: Relevance
“…HCI-AEs, including severe/fatal events, have been reported in patients who were infused with HSC products containing DMSO, but our prospective study of general recipients revealed that factors unrelated to the DMSO may also lead to HCI-AEs. 13,19 Since we were also aware of greater relative volumes of HSC products for small recipients, we herein report subgroup analysis for whole small recipients, including pediatric recipients, drawn from general recipients of our HCI-AE study. Among general recipients, the rates of overall HCI-AEs were significantly higher in allo-BMT compared with auto−/allo-PBSCT and allo-CBT.…”
Section: Discussionmentioning
confidence: 99%
“…HCI-AEs, including severe/fatal events, have been reported in patients who were infused with HSC products containing DMSO, but our prospective study of general recipients revealed that factors unrelated to the DMSO may also lead to HCI-AEs. 13,19 Since we were also aware of greater relative volumes of HSC products for small recipients, we herein report subgroup analysis for whole small recipients, including pediatric recipients, drawn from general recipients of our HCI-AE study. Among general recipients, the rates of overall HCI-AEs were significantly higher in allo-BMT compared with auto−/allo-PBSCT and allo-CBT.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the recognized detrimental effects the process of thawing has on cells, the presence of apoptotic or necrotic cells in the infused product risks introducing potentially detrimental immunological responses. [ 60 ]…”
Section: Discussionmentioning
confidence: 99%
“…Derivation of multiple FPC types from a single organ donation and the development of robust analytical technologies drastically simplify screening and testing processes during manufacturing (e.g., tests for sterility, isoenzyme typing, mycoplasma, viruses, prions, endotoxins, virus-like particles, retroviral activity, fungi, yeasts, bacteria, and tumorigenesis assays) (Applegate et al, 2009). Maximized safety, efficiency, and optimized industrial manufacturing schemes cost-enable innovative therapeutic developmental research and ensure on-demand availability of end-products (Haack-Sørensen and Kastrup, 2011; Abbasalizadeh et al, 2017;Pigeau et al, 2018;Hunt, 2019).…”
Section: Swiss Multi-tiered Biobanking Model For Primary Fpcsmentioning
confidence: 99%
“…2019b). Bioengineered products (e.g., cell-laden scaffolds), as considered herein for primary FPC delivery, are classified as combined ATMPs or TEPs, implying inherent substantial manipulations for standardized transplant elaboration, for which GMP requirements are derived from classical pharmaceutical industry guidelines (Johnson et al, 2011;Fisher and Mauck, 2013;Esteban-Vives et al, 2018, 2019. Such dangerous or hampering constraints have limited and eventually reduced the number of products and therapies reaching the market in Europe and are particularly problematic for University Hospitals in particular, as local regulators enforce supranational regulatory frameworks often in detrimental or jeopardizing ways concerning historically used and clinically proven therapies (e.g., cultured autografts for burn patients) (Gallico et al, 1984;Gallico and O'Connor, 1985;Hickerson et al, 1994;Wood et al, 2006;Cirodde et al, 2011;Auxenfans et al, 2015;Eder and Wild, 2019;Laurent et al, 2020i).…”
Section: Legal and Regulatory Framework For Fpcs And Product Developmentioning
confidence: 99%